Qualitative evaluation of a cognitive behaviour therapy Hearing Voices Group with a service user co-facilitator. Issue 1 (2nd January 2017) - Ruddle, Anna
Abstract : This project evaluated a Cognitive Behaviour Therapy (CBT) Hearing Voices Group (HVG), piloting the introduction of a service user co-facilitator (SUC). Interviews with the SUC and seven HVG attendees were analysed using thematic analysis. A superordinate theme was identified around what helped people "get something from the group", such as the process of "being in a group", including subthemes: "openness breeds openness" and "discovering I'm not alone'. Having an SUC was described positively, including subthemes: "relating to us" and "admiring resilience". A second superordinate theme around hindrances included societal barriers and "feeling anxious". A third superordinate theme of changes made by HVG members included developing "new perspectives" on themselves and their voices, "feeling inspired" by the SUC, and "coping better". The SUC found facilitating more valuable than attending an HVG. The study suggests that service users could be trained to co-facilitate structured CBT HVGs.